Impact of sustainability perception on consumption of organic meat and meat substitutes. (1st January 2019) - Siegrist, Michael; Hartmann, Christina
Abstract: Consumers' food selections have a large impact on the environment. In this study, we examined how consumers evaluated the environmental impact of various foods. Furthermore, we investigated whether the perceived environmental effect of foods, health consciousness, and food disgust sensitivity would be related to the consumption of meat substitutes and organic meat. We used data from the Swiss Food Panel 2.0 for our analyses ( N = 5586 participants from the German- and French-speaking part of Switzerland). The participants mistakenly perceived the environmental impact of soy-based meat substitutes as similar to that of conventionally produced meat. The results suggested that consumers with low meat consumption, perceptions about the high environmental impact of meat, high health consciousness, low disgust sensitivity, and who were female, younger, and better educated were more likely to consume meat substitutes compared with people who had the opposite attributes. Perceived environmental impact of conventionally produced meat, health consciousness, being female, age, income, and education had a positive impact on consumption of organic meat. Disgust sensitivity had a negative effect. The relatively low negative correlation between meat and meat substitute consumption implies that the substitution effect may not be as large as hoped for in the transition to more sustainable food behavior. However, our results also indicate that increasing consumer knowledge about the environmental impact of foods may lead to more sustainable food consumption.